A RARE CASE OF SOLITARY FIBROUS TUMOR AND PLEOMORPHIC RHABDOMYOSARCOMA OF THE NASAL CAVITY AND PARANASAL SINUSES - M. V. Naboka; V. K. Kossenok; V. A. Vodolazskiy; C. V. Maslennikova; S. P. Popov; V. P. Kazakovtsev; I. V. Ryabets (Сибирский онкологический журнал)
Solitary fibrous tumor is a rare neoplasm with the borderline biological nature and a tendency to the locally destructive growth. The most common site of the tumor is the pleura but other sites do occur. The ENT-organs are affected extremely rarely. A few cases of the nasal cavity and paranasal sinuses as the primary sites of this neoplasm have been described. Pleomorphic rhabdomyosarcoma occurs at these anatomic sites rarely as well. In the article a case of solitary fibrous tumor and pleomorphic rhabdomyosarcoma of the nasal cavity and paranasal sinuses manifested within 3 years is presented. Rhabdomyosarcoma had a fatal clinical course.